Constructing zwitterionic polymer brush layer to enhance gravity-driven membrane performance by governing biofilm formation. (1st January 2020) - Liu, Caihong; Song, Dan; Zhang, Wenjuan; He, Qiang; Huangfu, Xiaoliu; Sun, Shaofang; Sun, Zhiqiang; Cheng, Wei; Ma, Jun
Abstract: In this study, zwitterionic polymer brushes with controlled architecture were grafted on the surface of gravity-driven membrane (GDM) via surface-initiated reaction to impart antifouling property. A variety of membrane characterization techniques were conducted to demonstrate the successful functionalization of zwitterionic polymers on PVDF hollow fiber membrane. The membrane underwent 90 min of reaction time possessing strong hydrophilicity and high permeability was determined as the optimal modified membrane. Long-term GDM dynamic fouling experiments operated for 30 days using sewage wastewater as feed solution indicated zwitterionic polymer modified membrane exhibit excellent membrane fouling resistance thus enhanced stable flux. Confocal laser scanning microscopy (CLSM) imaging implied that zwitterionic polymer modification significantly inhibit the adsorption of extracellular polymeric substances (EPS) which dominates fouling propensity, resulting in the formation of a thin biofilm with high porosity under synthetic functions of foulants deposition and microbial activities. Interfacial free energy prediction affirmed the presence of zwitterionic functional layer on membrane surface could substantially decrease the interactions (e.g., electrostatic attractions and hydrophobic effects) between membrane and foulants, thereby reduced flux decline and high stable flux. Our study suggests surface hydrophilic functionalization shows promising potential for improving the performance of ultra-low pressure filtration. Graphical abstract: Image 1 Highlights: Zwitterionic polymers were grafted on PVDF HFM surface via ATRP with controlled architecture. Functionalized membrane exhibited improved stable flux under GDM dynamic fouling tests. Presence of zwitterion layer led to the formation of compressed biofilm with high porosity. Zwitterion grafting reduced membrane-foulant electrostatic and hydrophobic interactions.